PENGARUH EARNING PER SHARE, RETURN ON EQUITY DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM PADA PERUSAHAAN BATU BARA YANG TERDAFTAR DI BEI PERIODE 2015-2019 - Ayu Nirmala Sari; Evistiani Gulo; Arsiska F Situmorang; Jamaluddin Jamaluddin (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Observation of the research results has a specific purpose to test any effect of the variabels Earning Per Share, Return On Equity, and Net Profit Margin on the share price of Coal Companies on the IDX for the 2015-2019 period. The population for this study used purposive sampling by using two analytical techniques used, namely multiple linear analysis and hypothesis testing using SPSS (Statistical Product and Service Solutions). Results The contribution of the three variabels is 25.5% and 74.5% is influenced by other factors. So based on the results of research tests there is a conclusion that the results of the Earning Per Share, Return On Equity variabel have no significant effect on stock prices, and Net Profit Margin has a significant effect on stock prices. Then the results of the three variabels Earning Per Share, Return On Equity, Net Profit Margin have an effect on the domain or simultaneously on stock prices.